Analysis of the Influence of Education Costs, Quality of Educational Services, and References on Parental Satisfaction in Enrolling Their Children at SDIT Al-Kautsar Cikarang - Widianingsih Widianingsih; Fathorrahman Fathorrahman; Theresia Pradiani (Utan Kayu Publishing, 2025)
This study aims to analyze the influence of education costs, the quality of educational services, and references on parents' satisfaction in enrolling their children at SDIT Al-Kautsar Cikarang. The research used a quantitative approach with data collected through questionnaires distributed to parents of students. The independent variables in this study include the quality of educational services, education costs, and references, while the dependent variable is parents' satisfaction. The method applied is multiple linear regression with the assistance of SPSS 26 software. The sampling technique used was the Slovin method, with 95 respondents comprising parents of students in grades II-VI at SDIT Al-Kautsar Cikarang. The results show that education costs, the quality of educational services, and references have a significant simultaneous and partial effect on parents' satisfaction. The quality of educational services is the most dominant factor influencing parents' satisfaction, followed by education costs and references. These findings suggest that improving the quality of educational services and implementing effective communication strategies related to costs, as well as reference management, can enhance parents' satisfaction with the school. This study is expected to contribute to the management of SDIT Al-Kautsar Cikarang in developing strategies to improve educational services, refine cost management systems, and create reference-based promotion strategies to strengthen parents' trust and satisfaction.